PENDAFTARAN HAK MEREK SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP INDUSTRI UMKM - Irma Abidahsari; Tegar Hartantha Pratama; Margaretha Andini Oktavina; Jason Sebastian Tunru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The activities of micro, small and medium enterprises as productive businesses are growing rapidly which is shown in the large number of MSME actors in Indonesia. Brands are important in the running of Micro, Small and Medium Enterprises (MSMEs). This is motivated by the fact that there are still at least MSME actors who register their trademark rights legally, compared to those who do not register their trademark rights. The author in this paper aims to find out related to MSME Brand Rights, and can find out the existing Legal Protection of MSME Brand Rights. The method taken by the author here is a descriptive qualitative method. At the point of the research results, the author takes 2 cases of trademark rights disputes that have occurred in Indonesia and the discussion and conclusion that brand rights as the identity of UMKM products with a lack of awareness of UMKM actors to register trademark rights legally which is associated with the example of Ruben Onsu's trademark lawsuit case to PT Ayam Geprek Benny Sujono